The Effect of Training, Occupational Safety, Health and Work Motivation on Employee Performance at PT. Amal Tani Langkat - Reza Ramadan Ginting; Hasrul Azwar Hasibuan (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to examine and provide a clearer understanding of the effect of training, occupational health and safety, and work motivation on employee performance at PT Amal Tani Langkat. This research employs a quantitative method with a total of 45 respondents. The data were analyzed using statistical formulas and processed with SPSS version 26. The results indicate that training has a positive and significant partial effect on employee performance at PT Amal Tani Langkat, as evidenced by the t-test results with a t-value of 4.418 > t-table 2.018 and a significance value of 0.000 < 0.05. Occupational health and safety also have a positive and significant partial effect on employee performance at PT Amal Tani Langkat, as shown by the t-test results with a t-value of 2.313 > t-table 2.018 and a significance value of 0.026 < 0.05. Furthermore, work motivation has a positive and significant partial effect on employee performance at PT Amal Tani Langkat, as proven by the t-test results with a t-value of 5.775 > t-table 2.018 and a significance value of 0.000 < 0.05. Simultaneously, training, occupational health and safety, and work motivation have a significant effect on employee performance, as indicated by the F-test re